THE SPEECH ACTS OF COMPLIMENTS AMONG JAPANESE TEENAGERS IN JAPANESE ANIME FILMS - Diana Kartika; Farras Junior Riza (UIN Raden Mas Said Surakarta, 2022)
This study aimed to identify the forms of expressive speech acts of compliments and to describe the forms of perlocutionary acts that appear in the anime Yahari Ore no Seishun Love Come wa Machigatteiru and ReLife. This research used Searle’s speech act theory, Holmes' complimenting speech act, and Alston’s verbs of perlocutionary. The study applied descriptive method. The data were collected from observation and notes based on the techniques for analyzing direct elements. The data were presented in an organized set of information, allowing for conclusions and action analysis. Based on the results of the research, it was found that expressive speech acts in the forms of compliments were dominantly influenced by the speaker's ability. Meanwhile, the dominant perlocutionary verbs in the compliments refer to encouraging, irritating, and attracting attention.